2017
DOI: 10.1515/cjal-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Faceted Morphological Awareness and Vocabulary Knowledge in English as a Second Language Learners: A Multivariate Analysis

Abstract: This study investigates the role of morphological awareness in ESL vocabulary acquisition. Participants were 198 Chinese college students enrolled in a joint program which required them to study in China for the first two years and then study in the U.K. to complete their degrees. They completed a total of four paper-and-pencil tests: morpheme discrimination, morpheme recognition, vocabulary size test (VST) and word associates test (WAT) tests. We drew upon path analysis to explore the interconnected relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…Their findings showed that the various dimensions of lexical knowledge had different patterns of development, with spelling benefitting most from the first few exposures, knowledge of meaning requiring between three to seven exposures, and knowledge of parts of speech developing smoothly across exposures. The Chen and Truscott study is representative of many studies adopting the dimensions approach in that a narrow number of lexical items are tested in depth, rather than a broader yet shallower view of a range of lexical items (e.g., Fitzpatrick, 2012;Haomin & Bilü, 2017;Read, 1998).…”
Section: Lexical Depthmentioning
confidence: 99%
See 3 more Smart Citations
“…Their findings showed that the various dimensions of lexical knowledge had different patterns of development, with spelling benefitting most from the first few exposures, knowledge of meaning requiring between three to seven exposures, and knowledge of parts of speech developing smoothly across exposures. The Chen and Truscott study is representative of many studies adopting the dimensions approach in that a narrow number of lexical items are tested in depth, rather than a broader yet shallower view of a range of lexical items (e.g., Fitzpatrick, 2012;Haomin & Bilü, 2017;Read, 1998).…”
Section: Lexical Depthmentioning
confidence: 99%
“…Of the two, lexical depth is more challenging to define and measure due to its multi-dimensional nature (Haomin & Bilü, 2017;Schmitt, 2010) and because breadth and depth grow in relation to one another (Milton, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kirby et al, 2012;Li & Chen, 2016), and receptive vocabulary (e.g. Akbulut, 2017;Haomin & Bilü, 2017;Khodadoust, Aliasin, & Khosravi, 2013;Kraut, 2015;Latifi, Kasmani, Talebi, & Shirvani, 2012;Sparks & Deacon, 2015;Sumarni, 2016;Tabatabaei & Yakhabi, 2011;Varatharajoo, 2016;Yucel-Koc, 2015;Zhang & Koda, 2012). The relationship between morphological awareness and learners' spelling skills has also been examined (e.g.…”
Section: Introductionmentioning
confidence: 99%